Development of Interactive Teaching Materials Using Whiteboard Animation for Civic Learning in Elementary School - Tahmid Sabri; Soeharto Soeharto; Ikhsan Kurniadi (EDUCATIO : Journal of Education, 2019)
This study aims to describe the development designed of whiteboard animation interactive teaching materials and student behavior as long as they used interactive whiteboard animation teaching materials for civic learning in Elementary schools. This study used the Hannafin & Peck development model and the researcher has modified it, which consists of three main processes the needed assessment stage, the designed stage, and the development implementation phase1. Before the implementation of product trials, validation was carried out by material experts and ICT learning experts. Individual test subjects were 3 students, Small group trials were conducted by 9 students and a large group trial of 15 students. The results of the study described the design of interactive whiteboard animation for teaching material products by using the analysis stage, designed phase, and development implementation phase produced. Interactive teaching material products get categories “very good” when learned civic learning in elementary schools; student learned behavior when they used whiteboard animation teaching materials in terms of motivation, getting the category of "good" and from the aspect of learning activity getting the category of "good" in the learning process.